Data on ground ice, organic carbon and soluble cations in tundra permafrost and active-layer soils near Lac de Gras in the Slave Geological Province, N.W.T., Canada - Rupesh, Subedi; Kokelj, Steven V.; Gruber, Stephan (Zenodo, 2020)
Data and computer code for producing figures for the manuscript: Subedi, R., Kokelj, S. V., and Gruber, S.: Ground ice, organic carbon and soluble cations in tundra permafrost soils and sediments near a Laurentide ice divide in the Slave Geological Province, N.W.T., Canada. The Cryosphere, accepted for publication inOctober 2020. Discussion paper and final version: https://doi.org/10.5194/tc-2020-33 ========================================================================================== CONTENT OF DIRECTORIES ========================================================================================== -– data [input data to produce plots] |–– BoreholesMeta.csv |–– brackets_photos_ice.csv |–– brackets_photos_thawed.csv |–– Lac_de_Gras_permafrost_20200612.csv |–– NordicanaD |–– ds_000582159 [authoritative copy at doi:10.5885/45558XD-EBDE74B80CE146C6] |–– Cored_Drill_TCR.csv |–– Cored_Drill_TCR.csv_ReadMe.txt |–– ds_000582163 [authoritative copy at doi:10.5885/45558XD-EBDE74B80CE146C6] |–– Cored_Drill_Logs.csv_ReadMe.txt |–– Cored_Drill_Logs.csv –– plot [R scripts write plots into this subdirectory] –– src [R scripts to generate plots] |–– Combined_Plots.R [produces Figures 3–6] |–– Eskers.R [helper function called by Combined_Plots.R] |–– Organics.R [helper function called by Combined_Plots.R] |–– plot_boreholes_DD_single.R [produces Figures S3] |–– plot_boreholes_DD.R [produces raw Figure S2 for further graphic processing] |–– Till.R [helper function called by Combined_Plots.R] |–– Valley.R [helper function called by Combined_Plots.R] ========================================================================================== RUNNING SCRIPTS ========================================================================================== Adjust the variable 'path' in these scrips, then run: Combined_Plots.R plot_boreholes_DD_single.R plot_boreholes_DD.R Tested with R version 3.6.3 (2020-02-29) -- "Holding the Windsock" ========================================================================================== REFRERENCE ...